Students' Competence in the TOEFL Structure and Written Expression - Nuur Insan Tangkelangi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This study aims to find out the students' competence in answering questions on TOEFL structure and written expression. It mainly focused on Information and Technology students because the current curriculum in the institution requires them to take TOEFL. Ninety-two students from three different classes participated in this study. Data collection was done by utilizing an adopted test consisting of 40 questions was used. The data shows that the students' competence in the TOEFL structure and written expression is low. It is revealed by observing the mean scores of the students, namely 23.75 (class A), 27.5 (class B), and 42.5 (class C). One of the main reasons to explain this scenario is due to their poor English Grammar. Therefore, the study suggests the students should be guided in learning basic-to-advanced level of English Grammar before introducing them to the TOEFL's structure and written expression.